The Lonely Sense: The Autobiography of a Psychic Detective by Robert Cracknell and Colin Wilson - McLuhan, Robert (Journal of Scientific Exploration, 2013)
Everyone interested in pseudoscience, fringe science, anomalistics, is likely to benefit from the material in this work. The book has much to say about the social and political context in which heterodox claims about matters of science have flourished and been argued over since the middle of the 20th century. Creationism and Lysenkoism as well as Velikovsky are discussed quite comprehensively and informatively. Attempts within unorthodoxies to maintain a monolithic paradigm are illustrated and analyzed to good purpose. The Pseudoscience Wars uses the Velikovsky episode as entrée to examine how scientists and society behave when drastically unorthodox claims about matters of science are ventured by non-scientists; the Velikovsky affair "was about science in the postwar public sphere" (p. 22); "an abiding anxiety about science's relation to the 'public'" (p. 47) was central in the reaction of the scientific community. Much of the material is drawn from the Velikovsky Archives and some of it is likely to be new to most readers; in other ways as well the book illustrates the wide-ranging familiarity with pertinent literature that historians somehow manage to command, enabling them to recapture comprehensively the ambience of past eras.